Whiting up : whiteface minstrels & stage Europeans in African American performance - McAllister, Marvin Edward, 1969- (The University of North Carolina Press, 2011)
In this work, McAllister defines and explores whiting up, a long tradition in which African American actors, comics, musicians, and even everyday people have assumed white racial identities in a performative context. Whether in 19th century minstrel shows, in stage European performances where black actors take on white roles on the conventional stage, in musicals and satires crafted by a variety of African American dramatists, or in one-person shows by artists like Anna Deavere Smith, McAllister argues that this form of cross-racial play creates unexpected intercultural alliances even as it inc.